Exploring the economic case for climate action in cities. (November 2015) - Gouldson, Andy; Colenbrander, Sarah; Sudmant, Andrew; McAnulla, Faye; Kerr, Niall; Sakai, Paola; Hall, Stephen; Papargyropoulou, Effie; Kuylenstierna, Johan
Highlights: The first detailed assessment of the economic case for investing in low-carbon cities. Finds that there is a compelling economic case for cities to invest in low-carbon development. Investments in cost-effective options could reduce urban carbon emissions by 15–24% relative to business as usual over the next 10 years. Investment of 0.4–0.9% of city GDP per year would generate savings of 1.7–9.5% of city GDP by 2025. Highlights the need to build multi-level governance capacities to allow cities to exploit these opportunities. Abstract: There is increasing interest in the potential of cities to contribute to climate mitigation. Multiple assessments have evaluated the scale and composition of urban GHG emissions, while others have evaluated some aspects of urban mitigation potential. However, assessments of mitigation potential tend to be broadly focused, few if any have evaluated urban mitigation potential on a measure-by-measure basis, and fewer still have considered the economic case for investing in these measures. This is a significant knowledge gap as an economic case for action could be critical in building political commitment, strengthening institutional capacities, securing large-scale finance and targeting investment and implementation in cities. In this paper, we conduct a comparative analysis of the results of five recently completed studies that examined the economic case for investing in low-carbon measures in five cities: Leeds in the UK, Kolkata in India, Lima in Peru, Johor Bahru in Malaysia and Palembang in Indonesia. The results demonstrate that there is a compelling economic case for cities in both developed and developing country contexts to invest, at scale, in cost-effective low-carbon measures. The results suggest that these investments could generate significant reductions (in the range of 15–24% relative to business-as-usual trends) in urban carbon emissions over the next 10 years. Securing these savings would require an average investment of 3.2 billion per city, which if spread over 10 years equates to 0.4–0.9% of city GDP per year. However, the savings generated in the form of reduced energy bills would be equivalent to between 1.7% and 9.5% of annual city-scale GDP, and the average payback period of investments would be approximately 2 years at commercial interest rates. We provisionally estimate that if these findings were replicated and similar investments were made in cities globally, then they could generate reductions equivalent to 10–18% of global energy-related GHG emissions in 2025. While the studies offer some grounds for optimism, they also raise important questions about the barriers to change that prevent these economically attractive options from being exploited and about the scope for mitigation based on the exploitation of only the economically attractive options. We therefore discuss the institutional capacities, policy environments and financing arrangements that need to be developed before even these economically attractive opportunities can be exploited. We also demonstrate that, in rapidly growing cities, the carbon savings from such investments could be quickly overwhelmed – in as little as 7 years – by the impacts of sustained population and economic growth. We conclude by highlighting the need to build capacities that enable the exploitation not only of the economically attractive options in the short term but also of those deeper and more structural changes that are likely to be needed in the longer term.